Insulin Pump Therapy is Equally Effective and Safe in Elderly and Young Type 1 Diabetes Patients (The Review of Diabetic Studies, 2023)
OBJECTIVES: It is generally accepted that in adult type 1 diabetes patients (T1D) continuous subcutaneous insulin infusion (CSII) via a personal pump is more effective than the multiple daily injections (MDI) model. However, it is not clear whether all age groups of adult T1D patients may equally benefit from CSII therapy. We aimed to compare the glycemic control and use of selected pump tools in T1D subjects using CSII over the age of 50 (50+ T1D) with patients younger than 50 years of age. METHODS: The last available insulin pump/blood glucose meter downloads and last available HbA1c levels of 124 adult T1D subjects using CSII were reviewed. We divided our cohort into two subgroups: 50+ T1D patients (n = 13) and younger patients (n = 111). RESULTS: There were no differences in glycemic control achieved with CSII treatment in 50+ T1D patients vs. younger subjects. HbA1c levels were 7.01 ± 0.67% and 7.34 ± 1.24% (p = 0.46), and the mean glycemia based on glucometer downloads was 141.8 ± 17.7 mg/dl and 150.8 ± 35.7 mg/dl (p = 0.69), respectively. Also, there were no differences with respect to the use of important personal pump options and tools. CONCLUSION: In conclusion, insulin pump therapy appears to be effective and safe in T1D patients regardless of age.